Level Studies of Some Mass 89 Nuclei - Kitching, ﻿James Edgar (My University, 1966)
The decay of 14.9 min. ⁸⁹Rb to levels in ⁸⁹Sr has been studied by use of Ge(Li) detectors, NaI(Tl) detectors and a magnetic beta ray spectrometer. Fourteen gamma rays have been studied by ɣ-ɣ and β-ɣ coincidence experiments and establish levels at 0, 1.031, 2,000, 2.277, 2.567, 2.708, 2.770, 3.225 and 3.500 MeV. The Q value is 4.486 ± .012 Mev.
The techniques of beta and gamma ray spectroscopy using Ge(Li), NaI(Tl) and plastic beta detectors have been applied in the study of the decay of 3.2 min. ⁸⁹Kr to levels in ⁸⁹Rb. Seventy nine of the one hundred and eleven observed gamma rays have been classified in the proposed decay scheme. The Q value is 5.15 ± .03 MeV.
Missing page viii. Page 171 was repeated with different text.
Keywords: level studies; mass 89 nuclei; Rb-89; Sr-89; Kr-89; Ge(Li) detector; NaI(Tl) detector; magnetic beta ray spectrometer; gamma ray spectrometry